Genotypic and Phenotypic Identification of Dermatophytes among Clinical Isolates - Datt, Shyama; Datt, Thakur; Singh, Narender Pal (Jurnal Ilmu Kesehatan dan Kesehatan, 2025)
Background: The prevalence of superficial fungal infections varies basedon environmental and hygienic conditions. Dermatophytes, particularlyTrichophyton rubrum and T. mentagrophytes, are keratinophilic fungiresponsible for the majority of these infections. Their ability to produceproteases and keratinases active at acidic pH facilitates colonization ofhuman skin. This is a fundamental mechanism observed in Trichophytonrubrum and Trichophyton mentagrophytes in establishing superficialinfection.Methods: A total of 200 clinical samples from patients with suspecteddermatophytosis were examined using potassium hydroxide (KOH) mountand culture techniques. Culture-positive isolates were further identifiedthrough conventional mycology and molecular methods, including PCR andsequencing using species-specific ITS2 primers for T. rubrum and T.mentagrophytes. Clinical profiles, treatment history, and recurrence patternswere also analyzed.Results: Among 200 KOH-positive samples, 140 yielded culture-positiveresults, of which 60 isolates were identified as dermatophytes. Molecularidentification confirmed 20 isolates as T. rubrum and 40 as T.mentagrophytes. Clinically, 43.34% of cases were naïve infections, 50%had ongoing antifungal treatment for 1–2 years (recalcitrant cases), and6.66% were categorized as reinfections due to recurrence of lesions posttherapy. The mean patient age was 30.02 ± 10.95 years, with a male-tofemale ratio of 2:1.Conclusion: Trichophyton mentagrophytes was more prevalent than T.rubrum among dermatophyte-positive cases. The high rate of recalcitrantand recurrent infections highlights the need for accurate species-leveldiagnosis using molecular tools to guide effective antifungal managementstrategies.